THE IMPLEMENTATION OF COLLABORATIVE TEACHING MODEL IN TEACHING GRAMMAR AT SMK MUHAMMADIYAH PIYUNGAN - Umi Solikhah (JELLT (Journal of English Language and Language Teaching), 2019)
This research aims to 1) describe the implementation of collaborative teaching model in teaching grammar at SMK Muhammadiyah Piyungan.and 2) describe the strengths and limitations of the collaborative teaching model implemented in teaching grammar at SMK Muhammadiyah Piyungan. The research was categorized into descriptive qualitative using case study design. The subjects of this study were 18 students of class X TKR A of SMK Muhammadiyah Piyungan in Academic Year 2018/2019. The main data of this research were gained by conducting classroom observation and questionnaire for the students that were analyzed descriptively qualitatively. The findings of the study indicated that the implementation of collaborative teaching model in teaching grammar at SMK Muhammadiyah Piyungan followed teaching procedures of PPP method. They were Presentation, Practice, and Production. Besides, the researcher found the strengths and limitations of the collaborative teaching model implemented in teaching grammar at SMK Muhammadiyah Piyungan. The strengths were 1) The students had more opportunities in asking the materials; 2) The students got their attention back when the pre-service teacher 2 (LZ) and pre-service teacher 3 (DM) approached them; 3) The pre-service teachers helped each other in managing the students; 4) The students felt happy toward the learning process. Otherwise, this model also brought the limitation such as the students might get confused because there was more than one teacher in the classroom.